Особенности разработки математических моделей электрических машин для виртуальных испытательных стендов - Милых, Владимир Иванович; Майстренко, Алексей Михайлович (Институт электродинамики, 2008)
The paper presents a specific approach in mathematical modeling for virtual electric machine laboratory. Also the certain practical results of implementing of virtual electric machine laboratory overviewed. Virtual electric machine laboratory presented also as a tool for teaching of intelligence control and drive systems
Keywords: графические модели; виртуальная реальность; системы приводов; electric machine modeling; electric machine laboratory; virtual reality; drive systems; intelligence control systems